Development of the STS marker for marker-assisted selection of drought resistance in rice - Thuy, Le Bich; Thanh, Nguyen Duc (Academia Journal of Biology, 2015)
The biotechnology has a great potential for plant breeding as it promises to reduce the time to be taken in breeding program. In recent years, new tools of the cellular and molecular biology such as the molecular marker techniques and the marker-aided selection have been extensively used. In this study, we attempt to develop the STS marker linked to the locus which are proved to be favored for the drought resistance, for the evaluation and the selection of the drought resistance in rice. Nine STS primers were used to amplify the genomic DNA from two parents and a segregating population. All the PCR products show no polymorphism between parents and progenies. Then the PCR products were digested with seven restriction enzyms, the obtained results showed that the STS G20 primer pairs developed the base on end sequences of the RFLP markers linked to maximum root length were, successfully, reviled polymorphism between parents and progenies. The results on the evaluation of root trait showed that all the progenies having HinfI restriction enzym patterns as male parent have the root trait (maximum root length) favour for the drought resistance. Thus, the STS G20 could be an useful marker for the evaluation and selection of the drought resistance in rice.